Development of a renewable hybrid power plant with extended utilization of pumped storage unit equipment - Makhotilo, Kostiantyn; Chervonenko, Ivan; Saad El Masri, Alaa Halim (Eastern-European Journal of Enterprise Technologies, 2019)
The scheme of a renewable hybrid power plant with the extended use of the installed equipment of the pumped storage unit for the conversion of the photovoltaic and wind generators direct current to the alternating one is proposed. The scheme is based on existing components with widely used proven technology. To output the power of solar and wind generators to the grid and for DC to AC conversion, a synchronous generator of the pumped storage unit is used in addition to grid inverters. An induction motor, powered through a variable frequency drive from a common DC bus, is used together with a hydraulic turbine to rotate the generator. In addition, batteries and capacitors banks are connected to the DC bus. The possibility of using various types of electric machines to drive a synchronous generator is analyzed and the preference of an induction motor is shown. The response of an induction motor to rotational speed fluctuations is modeled and its capability to participate in the network frequency regulation is shown. With the example of a typical daily load and generation profile, it is shown that the proposed solution for DC to AC conversion has an efficiency close to that of the grid inverter. The proposed scheme of the hybrid power plant can increase the reliability of renewable energy sources and the stability of the network frequency. This is achieved due to increasing the inertia of the rotating masses in the power system, the power factor control capabilities of the synchronous generator and the proper response of induction motor to rapid fluctuations of the rotation speed. The creation of such hybrid power plants opens the way for a further increase in the share of renewable energy sources in the power system